Is bad breath associated with dyspepsia? An association and an equivalence study - Nádia Cristina Pinheiro RODRIGUES; Alexandre ABRÃO NETO; Paulo NADANOVSKY (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract Halitosis affects all populations worldwide. The presence of chronic halitosis may be related to a health problem. Patients with bad breath usually seek a gastroenterologist and, in some cases, invasive and expensive exams, such as digestive endoscopy, are performed to investigate the etiology of halitosis. This study aimed to investigate whether the prevalence of bad breath in patients diagnosed with dyspepsia (any pain or discomfort in the upper abdomen) is higher than or equivalent to that in non-dyspeptic patients. This is a cross-sectional study that included 312 patients from university hospitals in the city of Rio de Janeiro (141 dyspeptic patients and 171 non-dyspeptic ones). The presence of halitosis was defined based on different cutoff points. Association analyses were performed using a log-binomial model and 95% confidence intervals were calculated for the coefficients, adjusting for sex and age. The equivalence test (Westlake) was used to test the hypothesis of equivalence between the proportions of patients with bad breath in the two groups (dyspeptic vs. non-dyspeptic), considering an equivalence band of ± 15%. The prevalence of bad breath ranged from 30% to 64% according to the definition of bad breath. Dyspepsia was not associated with bad breath in any of the three definitions of bad breath (two specific ones and a sensitive one). The proportion of patients with marked bad breath was equivalent in patients with and without dyspepsia.